Fiscal incidence of public expenditure on higher education in South Africa. A comparison between 2000 and 2006 - de Villiers, Pierre (South African Journal of Higher Education, 2016)
Currently no distinction is made in the financing of higher education in South Africa with respect to race. One would thus expect all racial groups to receive the same subsidy per student. This paper investigates whether it actually works out this way in reality. The analysis is done for 2000 and 2006 and estimated subsidies are calculated per headcount of students as well as full time equivalent student numbers. A further distinction is made between calculations for all students and for only contact students. In the last instance a distinction is also made between those students studying in social sciences and those in natural sciences. From this analysis it follows that there is indeed differences in the subsidy paid per student and that Indian and white students still received the biggest subsidies. This is directly linked to the fact that a greater percentage of these students study in natural sciences (who receive a subsidy 2½ times more than the subsidy of students in social sciences) than is the case for African and coloured students. This unintended inequality must already be addressed at school level by encouraging a larger percentage of learners to take maths and/or science.